The art and science of teaching : a comprehensive framework for effective instruction - Marzano, Robert J. (Alexandria, VA : Association for Supervision and Curriculum Development, 2007)
Presents a framework for teachers, in the form of ten questions, to help them balance research-based data with strategies for engaging with students, help students interact with new knowledge, and maintain rules in the classroom.
What will I do to establish and communicate learning goals, track student progress, and celebrate success? -- What will I do to help students effectively interact with new knowledge? -- What will I do to help students practice and deepen their understanding of new knowledge? -- What will I do to help students generate and test hypotheses about new knowledge? -- What will I do to engage students? -- What will I do establish or maintain classroom rules and procedures? -- What will I do to recognize and acknowledge adherence and lack of adherence to classroom rules and procedures? -- What will I do to establish and maintain effective relationships with students? -- What will I do to communicate high expectations for all students? -- What will I do to develop effective lessons organized into a cohesive unit?
Includes bibliographical references (p. 193-212) and index.
Professional
Keywords: Classroom management -- United States; Effective teaching -- United States; Learning, Psychology of; Teaching -- Aids and devices; Classroom management; Psychology of learning; Teaching -- Aids and devices; Teaching -- United States